Isolation and Characterization of Campylobacter and Salmonella Species from Water Sources in Uttarakhand, India: Assessing Colistin Resistance in the Isolates - Ansari, Iram; Maansi; Kamboj, Aman; Upadhyay, A.K. (Veterinaria Italiana, 2025)
Waterborne diseases can affect a large number of individuals in a short span of time; hence the possibility of them turning into an outbreak is high. Zoonotic pathogens represent an important fraction as causative organisms of waterborne illnesses. WHO has ranked Campylobacter spp. and Salmonella spp. as the two leading zoonotic pathogens in the world. The aim of this study was to isolate and identify Salmonella and Campylobacter species from the surface water bodies in two districts of Uttarakhand, India- Udham Singh Nagar and Nainital. Water samples from various locations were analyzed for the presence of these bacteria, with the latter coming out to be the predominant one. Thereafter, they were tested for resistance against Colistin, an antibiotic considered to be the last resort antibiotic against gram-negative bacteria and for the presence of mcr genes as the cause behind the resistance. The number of isolates showing the presence of these genes was significantly higher as compared to a previous study where an attempt was made to test their presence.